DOA SEBAGAI BENTUK PERTUKARAN EKONOMI - Wida Ayu Puspitosari; Rona Bethari Sugianto (Jurnal Sosiologi Pendidikan Humanis, 2019)
This study discusses the practice of social exchange at joint prayer activities at the 'X' Orphanage in Sidoarjo. The joint prayer activities at the 'X' Sidoarjo Orphanage were routinely carried out by two main donors who at the same time became one of the main informants of this study. The purpose of this study is to know how to practice social exchange using the social exchange theory of George C. Homans. There are five propositions presented by Homans in his exchange theory which are the main discussion in this study. The method used in this study is descriptive qualitative with the subject of research as many as three main informants consisting of orphanage owners and two main donors to the orphanage. Data collection techniques are observation, interviews, and documentation. The results of this study show that social exchanges that occur between orphanages and donors in prayer activities together wrap exchanges that are actually economic. Where, both donors carry out joint prayers as a manifestation of the implementation of CSR programs and the obligation to pay zakat. This then has the effect of peace of mind for the two donors over the fall of economic and religious obligations inherent in both.